2010
DOI: 10.1002/pros.21214
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancer/testis antigens in prostate cancer is associated with disease progression

Abstract: Background The cancer/testis antigens (CTAs) are a unique group of proteins normally expressed in germ cells but aberrantly expressed in several types of cancers including prostate cancer (PCa). However, their role in PCa has not been fully explored. Methods CTA expression profiling in PCa samples and cell lines was done utilizing a custom microarray that contained probes for two-thirds of all CTAs. The data were validated by quantitative PCR (Q-PCR). Functional studies were carried out by silencing gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 31 publications
3
63
0
2
Order By: Relevance
“…PAGE4 is up-regulated in primary (organ-confined or localized), androgen-dependent PCa but not in advanced (metastatic), androgen-independent disease both at the mRNA level and at the protein level (31,35,36). Therefore, to discern the relevance of the posttranslational modification of PAGE4 by the two kinases in PCa, we determined their expression in both PCa cell lines and a benign prostatic hyperplasia (BPH) cell line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAGE4 is up-regulated in primary (organ-confined or localized), androgen-dependent PCa but not in advanced (metastatic), androgen-independent disease both at the mRNA level and at the protein level (31,35,36). Therefore, to discern the relevance of the posttranslational modification of PAGE4 by the two kinases in PCa, we determined their expression in both PCa cell lines and a benign prostatic hyperplasia (BPH) cell line.…”
Section: Resultsmentioning
confidence: 99%
“…33). However, PAGE4 protein expression is elevated in prostate cancer (PCa) (31,(34)(35)(36), where it is upregulated in response to a variety of stress factors (29,31). PAGE4 is phosphorylated at S9 and T51 by HomeodomainInteracting Protein Kinase 1 (HIPK1), a component of the cellular stress-response pathway, and functions as a strong potentiator of the oncoprotein c-Jun (32,37).…”
Section: Significancementioning
confidence: 99%
“…An increased humoral immune response to cancer testis antigen NY-ESO-1 was observed in the GAG-HERV-K Ab ĂŸ group. The presence of antibodies to cancer testis (CT) antigens has been associated with a worse prognosis in several cancer types including prostate cancer (32,38,52). The evidence of a co-immune response to GAG-HERV-K and NY-ESO-1 in a subset of patients with advanced prostate cancer suggests a potential biologic association between these 2 genes during prostate cancer progression and deserves to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Suyama et al 38 used a custom DNA microarray that was tiled with DNA probes representing a significant portion of all known CTAs to discern CTA expression patterns in prostate cancer. These studies revealed that: (i) numerous CTAs are upregulated in prostate cancer; (ii) a majority of them are CT-X antigens; and (iii) while several CT-X antigens from MAGEA/chondrosarcoma-associated gene (CSAG) subfamilies are coordinately upregulated in castrate-resistant prostate cancer but not in primary prostate cancer (Figure 1), PAGE4 is highly upregulated in primary prostate cancer, but is silent in castrate-resistant prostate cancer.…”
Section: Ctas As Potential Biomarkers In Prostate Cancermentioning
confidence: 99%
“…We first mined publicly available microarray data on CTA expression in prostate cancer samples from the Gene Expression Omnibus (GEO) (http://www.ncbi.nlm.nih.gov/ geo) in conjunction with our own data that we had previously obtained using a custom CT microarray 38 and selected a panel of candidate CTAs for investigation. The representative microarray data (GEO, accession no.…”
Section: Ctas As Potential Biomarkers To Discern Aggressive Phenotypementioning
confidence: 99%